Islam Wasathiyah di Ruang Digital: Perspektif Tokoh Muslim Indonesia - Baidawi, Baidawi; Rodliyah, Firda; Hanum, Siti Zaida (LP2M IAIN Palopo, 2025)
Wasathiyah Islam in the current context is faced with increasing violent content in the name of religion, the proliferation of religious populism, and the rise of radical discourse in virtual spaces. This article aims to map the role of Muslim figures who campaign for Wasathiyah Islam on digital media platforms so that the public can understand it clearly. This research uses a qualitative method based on literature study. Primary data is centred on narratives of Islamic wasathiyah through YouTube channels of four Indonesian Muslim figures, including Din Syamsudin, Quraish Shihab, Nasaruddin Umar, and Habib Husein Jakfar. Secondary data includes articles, journals, books, and digital traces about wasathiyah Islam. Data collection techniques focused on literature review and documentation. Data analysis techniques included data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that these four Muslim figures play a significant role in promoting wasathiyah Islam in the digital space as an effort to present a moderate Islamic perspective and emphasise the principle of tolerance. The content of moderate Islam as a religious knowledge offering to the public through the perspective of Muslim figures is not limited to disseminating Islamic values but also seeks to counter takfiri interpretations, block radical content, and combat the spread of hoax information on social media, which is currently spreading like a snowball effect and being exploited by various actors under the guise of religion. Keywords: Wasathiyah Islam, Digital Media, Muslim Figures